Cover feature: Photochemical and photocatalytic degradation of 1‐propanol using UV/H2O2: Identification of malonate as byproduct. Issue 18 (2nd September 2019) - Ferreira Santos, Mauro Sergio; Gomes Cordeiro, Thiago; Cieslarova, Zuzana; Gutz, Ivano Gebhardt Rolf; Garcia, Carlos D.
Abstract : DOI:10.1002/elps.201900001 The cover picture shows the photochemical and photocatalytical oxidation of 1‐propanol investigated by CE‐C 4 D. A simple experimental set‐up was used to irradiate 1‐propanol in the presence of TiO2 and/or H2 O2 . Propionic, acetic, formic and malonic acids were identified as byproducts of this reaction. Besides the environmental significance of these results, the identification of malonic acid, not previously reported, opens new avenues for the production of this important chemical building block.